"The Old White Lady of Kew Gardens", Hechtia argentea (Bromeliaceae: Hechtioideae), found her homeland in Mexico. Issue 5 (28th August 2020) - Ramírez‐Morillo, Ivón M.; Hornung‐Leoni, Claudia T.; González Ledesma, Manuel; Romero‐Soler, Katya J.
Abstract: Hechtia argentea was described from a cultivated pistillate plant of unknown origin. The type specimen consists of a leaf fragment and a portion of a pistillate inflorescence. Hechtia argentea is part of a group of species with rosettes that bloom laterally, showing variation in dimensions and structure of the inflorescences of both sexes through the different years of flowering. Delimitation of species becomes more complicated where staminate and/or pistillate plants of different species are frequently similar, making it essential to have all plant structures available for accurate identifications. We designate an epitype for Hechtia argentea, consisting of a staminate plant, allowing for the unambiguous identification of the species. Species in Hechtia have restricted geographical distributions; thus, we provide precise locality data for H. argentea within Megamexico based on herbarium specimens. The species is endemic to the Sierra Madre Oriental and Mexican Plateau biogeographical regions, in the Mexican States of Hidalgo and Querétaro. In addition, we include for the first time a complete morphological description of both morphs, line drawings and photos of the species in situ, as well as a map showing the known distribution. Finally, we present an evaluation of the risk of extinction following the IUCN criteria.